2019
DOI: 10.1371/journal.pone.0212024
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and temporal development of deltamethrin resistance in malaria vectors of the Anopheles gambiae complex from North Cameroon

Abstract: The effectiveness of insecticide-based malaria vector control interventions in Africa is threatened by the spread and intensification of pyrethroid resistance in targeted mosquito populations. The present study aimed at investigating the temporal and spatial dynamics of deltamethrin resistance in An . gambiae s . l . populations from North Cameroon. Mosquito larvae were collected from 24 settings of the Garoua, Pitoa and Mayo Oulo Health Dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 50 publications
0
27
0
Order By: Relevance
“…arabiensis is mainly a metabolic detoxification mechanism. However, over recent years, an increase in the prevalence of target-site resistance, kdr 1014F and 1014S alleles was also reported for this species [92, 167, 251]. Despite widespread distribution of kdr resistance alleles in An.…”
Section: Insecticide Resistancementioning
confidence: 99%
“…arabiensis is mainly a metabolic detoxification mechanism. However, over recent years, an increase in the prevalence of target-site resistance, kdr 1014F and 1014S alleles was also reported for this species [92, 167, 251]. Despite widespread distribution of kdr resistance alleles in An.…”
Section: Insecticide Resistancementioning
confidence: 99%
“…Several studies have reported spatial variation in resistance within a country, but these studies haven't analysed the spatial trends behind this variation [11,12]. In addition, time series of resistance data have shown changes over time at the location of sentinel sites [13][14][15][16][17][18][19][20]; however, only one study has investigated temporal trends across Africa [7]. This study generated a single trend over time for the whole continent, for each species and insecticide, and did not investigate differences in trends between locations.…”
Section: Introductionmentioning
confidence: 99%
“…Since 2015, deltamethrin has been the only pyrethroid reported to be used in mass IRS campaigns along with DDT and other non-pyrethroid insecticides [4]. Several studies have demonstrated a local increase in insecticide resistance in field mosquito populations following the implementation of LLINs, IRS, or both [19,20,[24][25][26] although in other locations evidence of higher resistance after the introduction of these interventions was not found [24,27]. Associations between agricultural pesticide use and insecticide resistance have also been found [21,28], and there is evidence that pesticide contamination of water bodies is a source of selection pressure for resistance acting on mosquito larvae [29].…”
Section: Introductionmentioning
confidence: 99%
“…Sources of insecticides in the environment include the application of insecticide-based vector control interventions for public health, such as LLINs and IRS, and the application of agricultural insecticides, which include the same insecticide classes as those used in vector control 11 . Several studies have demonstrated a local increase in insecticide resistance in field mosquito populations following the implementation of LLINs, IRS, or both 12, 13, 14, 15, 16 although in other locations evidence of higher resistance after the introduction these interventions was not found 12, 17 . Associations between agricultural pesticide use and insecticide resistance have also been found 11, 18 , and there is evidence that pesticide contamination of water bodies is a source of selection pressure for resistance acting on mosquito larvae 19 .…”
Section: Introductionmentioning
confidence: 99%